Automatic Cat Breeding and Drinking Equipment via Mobile Network Monitoring - Feranita, Feranita; Safrianti, Ery; Tambunan, Yuli Sartika (International Journal of Electrical, Energy and Power System Engineering, 2018)
This study aims to design a feeding and drinking tool for pet cats automatically based on SIM900A GSM Module. Design using GSM SIM900A, Arduino, RTC, load cell and Direct Current (DC) pump. This tool can be controlled to feed and drink the cat automatically at a distance. The working system of the tool consists of load cell 1, load cell 2 and water limit sensor which is an input result of measurement object which will be processed by arduino. Load cell 1 is used for measuring cat body weight, load cell 2 serves to measure cat feed weight and water limit function to enable and disable direct current pump. The pump will pump water to fill the cat drinking container if the container is empty. Data received by Arduino will be processed when the Real Time Clock (RTC) indicates the schedule of the cat’s feeder that has been set. Then the SIM900A GSM module will work sending short messages (SMS) to the mobile phone to inform the system has been working automatically feed the cat.